CARIES PROPHYLAXIS: JUST ANOTHER MYTH OR REALITY? - Yu.A. Fedorov; T.Yu. Soboleva ("Paediatrician" Publishers LLC, 2007)
Due to the fast (and drastic) changes of the oral care products market in Russia for the last 15-20 years, it's become feasible to evaluate the efficiency of caries fluorine prophylaxis. Despite the wide usage of fluorine content toothpastes, the rates of caries among children haven't actually changed. Moreover, in some regions a growth of frequency and intensity of this pathology has been witnessed, especially in younger age groups. At the same time, the introduction of new prophylaxis programs results in reduced rates of caries (decrease by 60-70%). This open wide opportunities for successful and efficient prophylaxis programs for kids and teenagers - both within organizations (schools, kindergartens, colleges) and individually by doctor's recommendation.Key words: children, caries, prophylaxis.